POTENSI DAN KELAYAKAN PENGEMBANGAN INSTALASI GIZI RSUD ARIFIN ACHMAD MENJADI PROFIT CENTER - Rina Yurianti; Heryudarini Harahap; Arnawilis Arnawilis; Budi Hartono; Siska Mayang Sari (PERSATUAN AHLI GIZI INDONESIA, 2021)
The development of dietary catering for outpatients is an opportunity to be one of the hospital profits centers. The study objective was to analyze the potential and the feasibility of the nutrition department as a profit center. The study design was cross-sectional. Data was collected through questionnaires and analyzed by descriptive and correlation analysis. The respondents were 70 inpatients families, 30 management hospital staff, and 32 nutrition department staff. A feasibility analysis was performed using Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), Payback Period (PP), and BEP (Break-Even Point). The results found that there was a relationship between willingness and capacity to pay for main meals (p = 0.013), with an average price of main food Rp. 16,193 ± 9,060 for portion. Respondents from management staffs who agreed to the nutrition department to be a profit center were 90.0 percent and all nutrition staffs. The market aspect was described from the 10 highest diseases of inpatients become a potential market as follow up treatment for post hospitalized patients. The technical aspect shows that the hospital is located in a strategic area and has adequate facilities. The organizational and management aspects show the support and commitment from top management, the commitment of nutrition department staff, and eligible human resources. The economic and financial aspects were described from NPV 0, IRR initial capital. The study conclusion was the Nutrition Department of RSUD AA has the potential to develop into a profit center and is feasible to implement.Keywords: feasibility study, nutrition services, profit center ABSTRAKPengembangan katering diet kepada pasien post rawatan merupakan peluang menjadi profit center dari Instalasi Gizi RSUD AA. Tujuan penelitian adalah untuk menganalisis potensi dan kelayakan pengembangan Instalasi Gizi RSUD AA menjadi profit center. Desain penelitian adalah cross-sectional. Pengumpulan data potensi dilakukan menggunakan kuesioner. Responden adalah 70 orang keluarga pasien, 30 orang dari manajemen, dan 32 orang dari instalasi gizi RSUD AA. Analisis potensi dilakukan secara deskriptif dan uji korelasi. Analisis kelayakan dilakukan dengan Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), Payback Periode (PP) dan BPE (Break Even Point). Hasil penelitian ditemukan ada hubungan antara kemauan dan kemampuan membayar makanan utama (p=0,013), dengan rata-rata harga makanan utama Rp. 16.193 ± 9.060 per porsi. Responden dari manajemen yang menyetujui Instalasi Gizi menjadi profit center adalah 90,0 persen dan semua responden dari instalasi Instalasi Gizi menyetujui menjadi profit center. Aspek pasar dapat dilihat dari 10 penyakit terbesar pasien rawat inap di RSUD AA tahun 2019 yang menunjukkan peluang pasar karena penyakit tersebut membutuhkan diet khusus tidak hanya selama perawatan di RS tetapi juga selama perawatan di rumah. Aspek teknis menunjukkan RSUD AA berada pada lokasi yang strategis, dengan luas yang memadai, dan fasilitas yang cukup. Aspek organisasi dan manajemen menunjukkan adanya dukungan dan komitmen dari top manajemen, komitmen pegawai instalasi gizi, organisasi pengelolaan instalasi gizi sudah mendukung dan jumlah tenaga yang mencukupi. Aspek ekonomi dan keuangan ditemukan dari NPV 0, IRR modal awal. Kesimpulan penelitian adalah Instalasi Gizi RSUD Daerah Arifin Achmad mempunyai potensi dalam pengembangan menjadi profit center dan layak untuk dilaksanakan.Kata kunci: pelayanan gizi, profit center, studi kelayakan